2015
DOI: 10.1089/chi.2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Childhood Obesity, Low Socioeconomic Status, and Race/Ethnicity: Lessons from Massachusetts

Abstract: Background: Previous studies have shown race/ethnicity, particularly African American and/or Hispanic status, to be a predictor of overweight/obese status in children. However, these studies have failed to adjust for low socioeconomic status (SES). This study assessed whether race/ethnicity remained an independent predictor of childhood obesity when accounting for variations in SES (lowincome) among communities in Massachusetts.Methods: This study was based on 2009 summarized data from 68 Massachusetts school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
109
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 40 publications
10
109
6
1
Order By: Relevance
“…This is consistent with published literature documenting primary payer status was an independent predictor of postoperative mortality, morbidity, and resource utilization for common pediatric surgical procedures . Further, post‐surgical infection rates and LOS are linked to obesity, a patient factor more common in children with low socioeconomic status . Although obesity can be coded for in KID, it is often underrecognized and may be underdocumented in billing codes.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with published literature documenting primary payer status was an independent predictor of postoperative mortality, morbidity, and resource utilization for common pediatric surgical procedures . Further, post‐surgical infection rates and LOS are linked to obesity, a patient factor more common in children with low socioeconomic status . Although obesity can be coded for in KID, it is often underrecognized and may be underdocumented in billing codes.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported that children from low SES families are at high risk of developing obesity (Dabrowska ; Rogers et al. ). Similarly, children living in developing countries experience higher rates of obesity than those in developed countries (WHO ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a low socioeconomic status has been associated with chronic conditions including diabetes, obesity, metabolic syndrome, alcoholism and hepatitis C; all of which are risk factors for cirrhosis and have been shown to increase the risk for HCC. 2,12,13 A plausible explanation for this is the expansion of accessibility to healthcare, and hence more patients in the lower income quartiles are being diagnosed and hospitalized with HCC and its complications. Furthermore, patients within a higher socioeconomic class are most likely to benefit from HCC screening and thus earlier detection.…”
Section: Discussionmentioning
confidence: 99%